2015
DOI: 10.1111/jcmm.12638
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stem cells enhance autophagy via PI3K/AKT signalling to reduce the severity of ischaemia/reperfusion‐induced lung injury

Abstract: Autophagy, a type II programmed cell death, is essential for cell survival under stress, e.g. lung injury, and bone marrow-derived mesenchymal stem cells (BM-MSCs) have great potential for cell therapy. However, the mechanisms underlying the BM-MSC activation of autophagy to provide a therapeutic effect in ischaemia/reperfusion-induced lung injury (IRI) remain unclear. Thus, we investigate the activation of autophagy in IRI following transplantation with BM-MSCs. Seventy mice were pre-treated with BM-MSCs befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…PI3Ks are a family of lipid kinases that regulate a wide variety of biological responses in many different cells (Li, Zhou, et al, ). PIK3CD, a subunit of PI3K, is known to be highly enriched in leukocytes and embryonic liver (Eickholt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3Ks are a family of lipid kinases that regulate a wide variety of biological responses in many different cells (Li, Zhou, et al, ). PIK3CD, a subunit of PI3K, is known to be highly enriched in leukocytes and embryonic liver (Eickholt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In damaged liver cells, MSC ameliorated liver fibrosis via activating autophagy, and human placenta‐derived mesenchymal stem cells also promoted hepatic regeneration by up‐regulating HIF‐1α and activating autophagy . BMSCs also attenuated lung injury by increasing the autophagy level via the PI3K/Akt signalling pathway . In this study, coculturing with BMSCs induced more intense autophagy than that in the hypoxia group.…”
Section: Discussionmentioning
confidence: 49%
“…Differentiation was also found to be another important aspect, as the transplanted BMSCs expressed several functional cell markers; however, the functions of the differentiated cells remain controversial . Recently, studies have shown that BMSCs can regulate autophagy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that autophagy of intrahepatic biliary epithelial cells (IBECs) may be involved in the pathogenesis of progressive bile duct loss in this disease . Mesenchymal stem cells (MSCs) are known to enhance the autophagy of cells against apoptosis . As a effective treatment to PBC, MSC transplantations applied to patients have been reported …”
Section: Introductionmentioning
confidence: 99%